Study of permittivity of saliva and urine to classify different stages of breast carcinoma / Ausilah Ahmad Sulieman Alfraihat - Ahmad Sulieman Alfraihat, Ausilah (2011)
Breast cancer is one type of disease that persists to have high incident rates among women. International agency for research on cancer (IARC) estimates more than one million cases of breast cancer happens yearly in the world and in each year large numbers of women pass away as a result of this disease. Despite of the variety of the modalities that can be utilized in the detection of breast cancer disease; these modalities still suffer of many drawbacks such as high false positive and negative rates accompanied with mammography, the side effects of the patient exposure to ionization radiation and the impracticability due to the high cost and time consuming for screening large population and, invasiveness of tissue biopsy. All of these weaknesses are a strong motivation for further investigation. Some evidences have been found that urine and saliva can be exploited as biomarkers for the detection of many diseases. The aim of this study was to evaluate the biomarkers of body fluids (urine & saliva) whether it can determine the stage of breast cancer. This is carried out by the measurement of the sample’s response to the applied microwave energy. The urine and saliva samples were measured by network vector analyzer between 10MHz to 20GHz. The significant differences in permittivity across the different stages were also investigated. Significance differences were found across all the groups in all parameters over certain frequency range, while no significant difference found in all dielectric parameters of saliva. The results suggest that it is possible to differentiate between different stages of breast cancer based on the dielectric properties of urine